Information and Perception towards Emergency Contraception among Female Adolescent Students in Secondary School of Kathmandu District - Karki, Binod Kumar (KMC Research Journal, 2019)
Emergency Contraception is a method used to avoid pregnancy after unprotected sexual intercourse or a contraceptive accident to prevent an unwanted pregnancy. This method has potential to prevent up to 75% of unplanned pregnancies. The aim of this study is to assess the information and perception towards emergency contraception among female adolescent students in secondary school.  Secondary classes (+2 Wing) run by Koteshwor Multiple Campus was selected as study area purposively. The study was conducted on November 2018 to December 2018. The study was based on descriptive cross-sectional research design. Self-administered structure and pre-tested questionnaire were used to obtain information and perception from 220 study participants were selected by simple random sampling technique. After data collection, the data was coded, entered, and analyzed by using SPSS version 20. The study shows that 84.5 percentages of the female adolescent students had heard about emergency contraceptive. 85 percentages of them identified the correct timing of use within 72 hours of unsafe sexual contact. 69 percentages respondents said they are ready to use emergency contraceptive if required. There is significant relation between educational level and information of emergency contraceptive. The level of information of emergency contraception among female adolescent students was high but perception towards that was negative while comparing to other studies.Thus,health education intervention regarding information and positive perception towards emergency contraception is needed to female adolescent students of secondary school.